2009
DOI: 10.1037/a0015588
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial to reduce club drug use and HIV risk behaviors among men who have sex with men.

Abstract: Objective-We examined the effectiveness of motivational interviewing (MI) on club drug use and risky sex in non-treatment-seeking men who have sex with men (MSM).Method-MSM (N=150) were assessed and randomly assigned to four sessions of MI or an educational control intervention. Follow up occurred at quarterly intervals for 1 year. Primary outcomes were days of any club drug use and number of unsafe sex acts.Results-On average, club drug use declined during follow up. A significant interaction effect showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 50 publications
4
68
0
Order By: Relevance
“…A recent systematic review by Lundahl and colleagues (2010) found that level of MI training did not influence the success of MI. Our results also indicated that 70% of the therapist's behavior in the MI treatment group was checked to be consistent with MI principles, often via coded audiotapes and structured behavior checklists (e.g., Morgenstern et al, 2009;Picciano et al, 2007). It seems providers were both competent in MI and likely adhered to the tenets of the intervention.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…A recent systematic review by Lundahl and colleagues (2010) found that level of MI training did not influence the success of MI. Our results also indicated that 70% of the therapist's behavior in the MI treatment group was checked to be consistent with MI principles, often via coded audiotapes and structured behavior checklists (e.g., Morgenstern et al, 2009;Picciano et al, 2007). It seems providers were both competent in MI and likely adhered to the tenets of the intervention.…”
Section: Discussionmentioning
confidence: 65%
“…Implicit in MI, as in most psychosocial models of behavior change, is the assumption that risk behaviors are largely under the control of the individual (Fisher & Fisher, 2000), and the intervention therefore risks failing to address the full range of factors that influences MSM's sexual behaviors, such as the strong interpersonal and social forces (see, e.g., Berg, 2008;Muñoz-Laboy & Dodge, 2007;Tieu et al, 2011). Among the three included studies in this systematic review that assessed the effectiveness of MI on both AOD use and sexual risk behaviors, two found an effect for AOD use but not sexual risk behaviors (Morgenstern et al, 2007;Velasquez et al, 2009), and the third found no effect for either outcome type (Morgenstern et al, 2009). Also previous efforts to reduce sexual risk behaviors using MI have yielded mixed results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, this corresponds to previous studies that have shown MI to be more effective in reducing substance use among the at-risk or mildly dependent, rather than for more severely dependent persons. 20 Reducing HIV-positive adolescents' alcohol use may also have beneficial effect on their medication adherence. Lower alcohol use has been associated with medication adherence among HIV-infected adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for each decision are given in Appendix 3. Articles were excluded for not being a RCT or other suitable study, as specified in our inclusion criteria; not having the sufficient percentage of MSM in the study population; [137][138][139][140][141][142][143][144][145] not including a sufficient percentage of HIV-negative participants; [146][147][148][149][150][151][152][153][154][155][156] or not being an individually focused intervention, instead focusing on groups or structural factors. [157][158][159][160][161][162][163][164][165][166][167] Other reasons for exclusion, such as interventions not being brief, reporting a pilot trial, reporting non-HIV-specific data (e.g.…”
Section: -106mentioning
confidence: 99%